THE INFLUENCE OF BOARD GAMES ON MATHEMATICAL SPATIAL ABILITY OF GRADE 9 STUDENTS IN JUNIOR HIGH SCHOOL - Chung, Chih; Yen-Chih, Hsu; Yeh, Ron; Lou, Shi (PEOPLE: International Journal of Social Sciences, 2017)
The main purpose of this study is to investigate the influence of board games on mathematical spatial ability of grade 9 students. This study used quasi-experimental design to enroll 2 classes of grade 9 students in a certain junior high school in the southern Taiwan as the research subjects. The subjects were divided into experimental group (28 subjects) and control group (29 subjects). This study performed the pretest, posttest, and experimental teaching for 7 times (once every 2 weeks; 2 classes each time). In the teaching experiment, this study used the implementation/non-implementation of board game activity teaching as the independent variable to investigate the influence of application of board games on mathematical spatial ability of grade 9 students in junior high school. Before the implementation of the experiment, this study used spatial ability scale to perform the pretest. After the implementation of the experiment, this study used spatial activity scale to perform the posttest. In the end, this study performed relevant statistical analyses, and collected students’ feedback slips and teachers’ teaching reflection. The research results showed that: (1) board game teaching improves students’ learning effectiveness of spatial ability; (2) board game teaching improves students’ learning interest in spatial ability; (3) after receiving board game teaching, the posttest showed that the mathematical spatial ability of students with more experiences in playing 3D animation games is significantly higher than that of those with less experiences in playing them; (4) the spatial perception, spatial identification, spatial rotation, and total score of mathematical spatial ability of the experimental group are significantly higher than those of the control group. According to the research results, this study proposed board game course of spatial ability for junior high school, and use computer network in combination with board game as reference for spatial ability teaching and subsequent studies.